Example of inverse functions, Algebra

Here are two one-to-one functions f (x ) and g ( x ) if

    (f o g )( x ) = x           AND                         ( g o f ) ( x ) = x

then we say that f ( x )& g ( x ) are inverses of each other. More particularly we will say that  g ( x ) is the inverse of f ( x ) and specified it by

                                                        g ( x ) = f -1 ( x )

Similarly we could also say that f ( x ) is the inverse of g ( x )and specified it by

                                           f (x ) = g -1 ( x )

The notation which we use really based upon the problem.  In most of the cases either is acceptable.

For the two functions which we started off this section along with we could write either of the following two sets of notation.

f ( x ) = 3x - 2                                           f -1(x) = x /3+ 2/3

g ( x ) = x/3 + 2/3                                 g -1 (x ) = 3x - 2

Now, be careful along with the notation for inverses. The "-1" is not an exponent in spite of the fact that is certain does look like one! While dealing with inverse functions we've got to keep in mind that

                           f-1(x)   ≠ 1/ f ( x )

Posted Date: 4/8/2013 1:22:22 AM | Location : United States







Related Discussions:- Example of inverse functions, Assignment Help, Ask Question on Example of inverse functions, Get Answer, Expert's Help, Example of inverse functions Discussions

Write discussion on Example of inverse functions
Your posts are moderated
Related Questions
(^5square root of 38)^3 Round your answer to 2 decimal places A.8.9 B.8.86 C.8.87 D.429.51

I really need help in this question (-5d + 1)(-2) I am really confused



2x+y/x+3y=-1/7and 7x+36y=47/3 hence find p if xy=p=x/y


By Using the discriminant find out which solution set we obatin for each of the following quadratic equations.                                           13x 2 +1= 5x Soluti

3u^3-5u^2-2u=0

In a earlier section we looked at graphing circles & since circles are actually special cases of ellipses already we've got most of the tools under our belts to graph ellipses.  Al

let x,y,z be the complex number such that x+y+z=2,x^2+y^2+z^=3,x*y*z=4,then 1/(x*y+z-1)+1/(x*z+y-1)+1/(y*z+x-1) is